2021
DOI: 10.1021/acs.jctc.0c01327
|View full text |Cite
|
Sign up to set email alerts
|

CHARMM36 Lipid Force Field with Explicit Treatment of Long-Range Dispersion: Parametrization and Validation for Phosphatidylethanolamine, Phosphatidylglycerol, and Ether Lipids

Abstract: Long-range Lennard-Jones (LJ) interactions have been incorporated into the CHARMM36 (C36) lipid force field (FF) using the LJ particle-mesh Ewald (LJ-PME) method in order to remove the inconsistency of bilayer and monolayer properties arising from the exclusion of long-range dispersion [Yu, Y.; et al. Semi-automated Optimization of the CHARMM36 Lipid Force Field to Include Explicit Treatment of Long-Range Dispersion. J. Chem. Theory Comput. 2021, 10.1021/acs.jctc.0c01326. (preceding article in this issue)]. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
113
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 88 publications
2
113
0
Order By: Relevance
“…Recently, a LJ cutoff-free version of C36 (C36/LJ-PME) was released. [45][46] The second TG model was made based on the C36/LJ-PME parameters in the same fashion used in the first model. However, both first and second models suffer from the low surface tension at the water interface (Fig.…”
Section: Aa-md Simulations and System Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a LJ cutoff-free version of C36 (C36/LJ-PME) was released. [45][46] The second TG model was made based on the C36/LJ-PME parameters in the same fashion used in the first model. However, both first and second models suffer from the low surface tension at the water interface (Fig.…”
Section: Aa-md Simulations and System Setupmentioning
confidence: 99%
“…Of note, DAG is also not included in the original C36 force field release; nonetheless, the CHARMM-GUI developers (The Im group) created a new topology for DAG based on the existing parameter set. All simulations were run by GROMACS 2018 and 2020 47 with the C36 43 , C36/LJ-PME [45][46] , or C36/LJ-PME-r force field. Simulations using C36 used the 1.2 nm LJ cutoff distance with a force-switching function between 1.0 nm to 1.2 nm, unless otherwise noted.…”
Section: Aa-md Simulations and System Setupmentioning
confidence: 99%
“…Fortunately, a solution to this problem has been recently proposed via the use of a PMElike treatment of the Lennard-Jones interactions in C36 (LJ-PME) (Yu et al 2021b, a). We thus opted to also develop C36 LJ-PME compatible parameters for TGs and DGs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is a well-known issue of the C36 lipid model (Yu et al 2021b, a) that, as shown for several alkanes and oils (Leonard et al 2018), originates from the cutoff-based treatment of LJ interactions.…”
mentioning
confidence: 99%
“…[12][13][14] This discrepancy has been suggested to arise from underestimated water-air surface tension of common water models 14,15 and the truncation of long-range van der Waals interactions which compromises the description of acyl chainvacuum interface. 13,16,17 We have recently demonstrated that the CHARMM36 ("C36" from now on) lipid model 13 combined with the 4-point OPC water model ("OPC4" from now on) 18 provides nearly quantitative agreement with experimental surface pressure-area isotherms of both singlecomponent 15 and multi-component 19 lipid monolayers. This is because OPC4 water model reproduces the surface tension of water with a Lennard-Jones (LJ) cuto↵ of 1.2-1.4 nm that is consistent with common lipid models such as the C36 13 and Slipids 20 ones.…”
Section: Introductionmentioning
confidence: 99%